Cervical cancer in Northern Tanzania—What do women living with HIV know - Mrema, Dorah; Ngocho, James Samwel; Mremi, Alex; Amour, Maryam; Machange, Rogathe; Shayo, Benjamin C.; Alloyce, Julius P.; Ndosi, Evaline; Shirima, Beatus T.; Fande, Device; Shehoza, Rahma; Balandya, Emmanuel; et al. (Frontiers in Oncology, 2023)
Abstract Background. Cervical cancer (CC) is more prevalent in women living with human immuno deficiency virus (HIV) infection compared to the general population. The magnitude is high among countries burdened with HIV - Tanzania is no exception. Despite the unprecedented risk, women living with HIV (WLHIV) may not be aware of the risk and might have unfounded beliefs thereof. This study aimed to determine the knowledge, awareness and beliefs on CC screening among WLHIV at-tending clinic at the Kilimanjaro Christian Medical Centre (KCMC) in the Northern Tanzania. Methods. This hospital-based cross-sectional study was conducted among 327 WLHIV attending care and treatment clinic (CTC) at KCMC. A pre-tested questionnaire was used to collect quantitative data. Both descriptive and regression methods were used to determine CC knowledge, aware-ness, and beliefs as well as factors associated with knowledge of CC among WLHIV using SPSS version 23. Results. Participants’ mean age was 46 ± 10.4 years. Although just half (54.7%) of WLHIV had in-sufficient knowledge of CC, the majority of the participants (83.5%) were able to recognize at least three risk factors, but with limited understanding of symptoms and prevention. The majority held positive beliefs on CC and screening practices. Factors associated with good knowledge of CC included being married [AOR: 3.66, 95%CI: (1.84-7.28)], having used ART for at least two years [AOR: 4.08, 95%CI: (1.36-12.21)], and having ever screened for CC [AOR: 1.62, 95%CI: (1.01-2.59)]. Conclusion. WLHIV attending care and treatment center had insufficient knowledge about cervical cancer. Such knowledge was associated with being married, having used ART for at least two years and having previously screened for CC. To further improve screening and treatment for CC, at both facility and community levels, targeted awareness and education campaigns are warranted.